Exploring Trust in the Police in South Korea During the COVID-19 Pandemic: Does Fear of the COVID-19 Matter? - Nam, Yongjae (Criminal justice review, 2024)
In response to the COVID-19 pandemic, governments restricted community members’ activities and, in turn, patterns of human behavior, both legal and illegal, changed. In many countries, the police have been entrusted to enforce these new COVID-19 related restrictions and were often perceived as the main enforcers of these sometimes unpopular measures. In this paper, we study four types of factors that may affect the public's trust in the police during the COVID-19 pandemic: traditional factors, such as interactions with the police during the pandemic, assessments of the police effectiveness in dealing with the pandemic, COVID-19 related factors, such as instrumental concerns for their personal health, and the adherence to the conspiracy theories. Specifically, using data from a sample of 527 respondents from the Seoul metropolitan area in South Korea, collected in the fall of 2021, we estimate the effects of the factors listed above. The results indicate that trust in the Korean National Police was strengthened when the police were perceived to have effectively dealt with the challenges of the pandemic and addressed the instrumental concerns of the community in the protection of public health. No demographic variables were significantly independently associated with trust in the police during the pandemic. The theoretical and policy implications of the findings are discussed.